(3fbT GdMfc ajeG bjd aj GdSecs - (3eMeO Hf Ydj Hf CMeO Hf Ydj Hf NeGQhjg Hf Whdhf GdOeTbqj GdUGdMj GdMfaj, TeS GdOjf , J (B953 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdeHOY deNdhaGJg Ydi ZjQ eKGd hHYO adeG ESJgd YGe CMO hYTQjf hJSYeGFI aCLHJ Cf CLeY dg eG EJab hef LeY CfhGYg eG EaJQb eSejkG dg HdbT GdMfc ajeG hQO ai GdSec s
(3BNQgG (B:s
(3hbO CJi YdjgG aQb GdYTQjf SfI hgj Ydi MGdgG hbO eOG HMQGc GdSec s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B291s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs